1997
DOI: 10.1037/0735-7028.28.5.437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the co-occurrence of substance use and other psychiatric disorders.

Abstract: The co-occurrence of substance use and psychiatric disorders is the rule rather than the exception in mental health and substance use treatment settings across the United States. Such co-occurrence may call for special assessment and evaluation procedures, modified treatment plans, and specialized follow-up. Treatment of co-occurrence of substance abuse and psychiatric disorders requires more cross-disciplinary collaboration; greater integration of substance use, mental health, and social services treatment ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…In other studies it was observed that patients with CMBD, especially those with more severe disorders, may have higher rates of aggression, detention due to illegal acts, suicide, relapses, spending on treatment, re-hospitalizations, longer hospitalization periods and greater medical service use 1 .…”
Section: Aspects Associated With the Clinical Conditions Assessedmentioning
confidence: 90%
See 3 more Smart Citations
“…In other studies it was observed that patients with CMBD, especially those with more severe disorders, may have higher rates of aggression, detention due to illegal acts, suicide, relapses, spending on treatment, re-hospitalizations, longer hospitalization periods and greater medical service use 1 .…”
Section: Aspects Associated With the Clinical Conditions Assessedmentioning
confidence: 90%
“…Such effects can remain for some days and disappear, unless these disorders are primary and continue to persist after many weeks of abstinence. For these reasons, it is recommended that a patient's follow-up should occur during a significant time for the diagnosis of other MBD to be reliable, and that this time could be different, depending on the PAS used 1 . A higher frequency of these disorders in Group 1 was observed in the present study, even if such diagnoses were considered to be positive when found throughout a certain period of time, rather than associated with recent PAS use exclusively.…”
Section: Frequency Of Diagnosis Of Cmbd Associated With CDmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be erroneously assumed by providers that the prime goal of detoxification services is the initiation of sustained sobriety, and that comorbid psychiatric symptoms will be relieved on their own, or will significantly diminish, once that objective is achieved. Rather, more positive overall outcomes are likely if treatment plans are designed to help alleviate both the alcohol use disorder and any comorbid psychological symptoms (Brems & Johnson, 1997;Grant et al, 2004). Attention to psychiatric symptoms among individuals in detoxification may greatly enhance their outcomes both with regard to sobriety and mental health, especially if detection is timed at the onset of their stay in detoxification and can thus be considered when additional treatment plans are made.…”
Section: Discussionmentioning
confidence: 99%